Plastic Waste to Energy,Tecthnology Solutions Based on Sustainability Criteria for Medium Size City in Latin America,Considering COVID-19 Pandemic - Juan P. Afanador; Ivon L. Bonilla; Viatcheslav V. Kafarov; Andrés F. León-Esteban; Lynda V. Carreño (Chemical Engineering Transactions, 2022)
In Colombia, solid waste constitutes one of the most important environmental problems that the State must face due to the difficulties in its management in most of the country's municipalities (Montes, 2018); the lack of environmental education, control measures and supervision exacerbate the current problem. Despite the existence of a legal framework and a comprehensive management plan for the treatment of this type of solid waste. It is possible that implementing the concepts of environmental footprint and LCA in the decision-making process on the implementation of new technologies for the treatment of plastic waste, it will allow minimizing the environmental impacts and the risks to human health provided by the waste. plastics related to COVID-19, especially in developing countries like Colombia. The main objective of this research is the selection of a set of technological solutions for the utilization and transformation of plastic waste through energy generation, considering the environmental, social, economic, and COVID-19 pandemic aspects. Case study: Bucaramanga, Colombia.